Forming the communicative competence of students at using the communicative technologies in the english lessons - Belgibayeva, G. K.; Baimakhan, A S.; Jan, Danek (Karagandy University of the name of acad. E.A. Buketov, 2023)
The article reveals the meaning of information and communication technologies, defines its role in teaching English in the context of modernization of education, and presents the classification of new information technology tools used in teaching English.
Keywords: information and communication technology; modernization of education; ICT tools; English language teaching; modem pedagogical technologies; English language teaching